2017
DOI: 10.1159/000450643
|View full text |Cite
|
Sign up to set email alerts
|

Carotid Intima-Media Thickness in Children Treated with Growth Hormone: A Follow-Up Study over Three Years

Abstract: Background: There is an ongoing discussion whether high doses of growth hormone (GH) may lead to cardiovascular diseases. Therefore, we studied the longitudinal relationships between GH treatment and carotid intima-media thickness (cIMT), which is predictive of the development of atherosclerosis. Methods: We measured blood pressure, lipids, hemoglobin HbA1c, IGF-1, IGFBP-3, and cIMT in 28 children treated with supraphysiological doses of GH (mean age 9.8 ± 2.2 years, 39% males) and 36 children suffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…A persistent very low IGF-1 level might have a protective role, whereas a milder decrease, such as in adult-onset GH-deficiency, might be predisposing to CVD risk ( 45 ). Rothermel et al ( 16 ) showed a correlation between cIMT and changes in IGF-1 SDS after rhGH treatment in GHD children, but not with the dose of the rhGH treatment. In our study, there was no association between IGF-1 SDS and cIMT-SDS.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A persistent very low IGF-1 level might have a protective role, whereas a milder decrease, such as in adult-onset GH-deficiency, might be predisposing to CVD risk ( 45 ). Rothermel et al ( 16 ) showed a correlation between cIMT and changes in IGF-1 SDS after rhGH treatment in GHD children, but not with the dose of the rhGH treatment. In our study, there was no association between IGF-1 SDS and cIMT-SDS.…”
Section: Discussionmentioning
confidence: 99%
“…In a cohort of children and adults consisting of 105 subjects over eight generations with GHD, there was no association between increased cIMT and GHD, but treatment with rhGH led to the appearance of carotid plaques ( 42 ). Rothermel et al ( 16 ) demonstrated cIMT increase in children treated for three years with a supraphysiological rhGH dose but not in those treated with a physiological dose. Another study did not demonstrate any change after four years of rhGH treatment in cIMT levels in a cohort consisting of children and adolescents receiving rhGH for various indications ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations